A mobile insulator system to detect and disrupt cis-regulatory landscapes in vertebrates - Bessa, José; Luengo, Mario; Rivero-Gil, Solangel; Ariza-Cosano, Ana; Maia, António H.F.; Ruiz-Ruano, Francisco J.; Caballero, Pablo; Naranjo, Silvia; Carvajal, Jaime J.; Gómez-Skarmeta, José Luis (Genome Research, 2014)
In multicellular organisms, cis-regulation controls gene expression in space and time. Despite the essential implication of cis-regulation in the development and evolution of organisms and in human diseases, our knowledge about regulatory sequences largely derives from analyzing their activity individually and outside their genomic context. Indeed, the contribution of these sequences to the expression of their target genes in their genomic context is still largely unknown. Here we present a novel genetic screen designed to visualize and interrupt gene regulatory landscapes in vertebrates. In this screen, based on the random insertion of an engineered Tol2 transposon carrying a strong insulator separating two fluorescent reporter genes, we isolated hundreds of zebrafish lines containing insertions that disrupt the cis-regulation of tissue-specific expressed genes. We therefore provide a new easy-to-handle tool that will help to disrupt and chart the regulatory activity spread through the vast noncoding regions of the vertebrate genome.
10.1101/gr.165654.113